Implementation of Project Based Learning Model Assisted by Honesty Campaign Poster Media to Improve Honest Attitudes and Learning Outcomes at SD Negeri Lam Geue - Arbani, T; Baihaqi (Program Studi Pendidikan Profesi Guru Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry Banda Aceh, 2025)
This study aims to describe the improvement of honest attitudes and learning outcomes of grade VI students of SD Negeri Lam Geue through the application of Project Based Learning (PjBL) assisted by Campaign Posters. This class action research (PTK) is carried out in two cycles, where each cycle consists of four stages, namely planning, action, observation, and reflection. The results of the study in the pre-cycle stage showed that the percentage of honest attitude of new students reached 45%, while the level of completeness of learning outcomes was 55%. After the implementation of actions in the first cycle, there was an increase with the percentage of honesty reaching 68% and the completeness of learning outcomes increasing to 70%. In cycle II, a more significant increase was seen with the percentage of honesty reaching 85% and the completeness of learning outcomes reaching 88%, which means that it has exceeded the established success indicators. Based on these results, it can be concluded that the application of the Project Based Learning (PjBL) learning model assisted by Campaign Posters is effective in improving the honest attitude and learning outcomes of Islamic Religious Education (PAI) students in grade VI at SD Negeri Lam Geue.